The job satisfaction of black female quantity surveyors - Punungwe, Fungai; Terblanche, Rolien (University of the Witwatersrand, Johannesburg, 2024)
Black women face discrimination in the quantity surveying profession hence experiencing tension to balance their careers and life, which results in them not being satisfied with their jobs. The aim of this research is to assess the job satisfaction of black females in quantity surveying and examine if discrimination affects it. Data was collected through online interviews with Black females that are Quantity Surveyors. The results were analysed using thematic analysis to assess similarities in responses. Issues of harassment discrimination were significantly recognised through deep interviews with participants. The issue of job satisfaction of black female quantity surveyors is less explored in literature. The findings of this research can be used by bodies of knowledge and industry professional to improve measures on issues of inequality and alleviate any problems.
This paper was presented at the Proceedings of the WABER SuDBE 2024 Conference, 30th – 31st July 2024, University of the Witwatersrand, Johannesburg, South Africa.
Keywords: Black female; Culture; Job satisfaction; Quantity surveyor; SDG-5: Gender equality